DETERMINATION OF THE INFLUENCE OF SURFACE-ACTIVE SUBSTANCES ON THE QUALITY OF COLORINGUNDER THE HETEROCAGULATION MECHANISM - Гараніна, О. О.; Редько, Я. В.; Корж, А. С. (Fashion Industry, 2020)
To determine the eff ect of the type and concentration of surfactants on the coloring quality of a water-insoluble analogue of a straight dye of cotton textile materials by the mechanism of heterocoagulation. Method. Heterocoagulation mechanism was used to obtain dyeing of cotton textile materials with water insoluble direct dye form. Sample software was used to determine the color characteristics of colored samples of textile materials. Appropriate standard methods were used to determine the strengths of the obtained colors. Results. The concentrations of surfactant required for the combination of suffi cient intensity of the dyeing with the required strength of the dyeing to dry friction are determined. The analysis of the results shows that not only the particle size but also the nature of the interaction of the dye surfaces and the fi brous material, which is responsible for the depth of the fi rst low of the DLFO theory (Deriagin, Landau, Fairway, Overbeck theory), is important for heterocoagulation dyeing. Direct dye may be in the form of nanodispersion. In this situation, the diff usion of the dye into amorphous sections of the polymer is excluded. Dyeing is carried out on ly due to heterocoagulation - deposition of dye particles on the surface of the fi brous material. It has been investigated that the dispersion particle deposited on the surface by the mechanism of heterocoagulation is secured by the forces of intermolecular interaction and its stability on the surface is ensured by the balance of the forces of intermolecular interaction and the infl uence of mo lecules of the dispersion medium (Brownian motion eff ect). With the successive reduction of the size of the dye particles to the nanoscale, the infl uence of the forces of intermolecular interaction increases signifi cantly. Practical importance. Reducing the cost of the dyeing process and preventing the detection of structural heterogeneities of textile materials is possible when using a heterocoagulation dyeing mechanism.